2013
DOI: 10.1371/journal.pone.0078535
|View full text |Cite
|
Sign up to set email alerts
|

Directional Locomotion of C. elegans in the Absence of External Stimuli

Abstract: Many organisms respond to food deprivation by altering their pattern of movement, often in ways that appear to facilitate dispersal. While the behavior of the nematode C. elegans in the presence of attractants has been characterized, long-range movement in the absence of external stimuli has not been examined in this animal. Here we investigate the movement pattern of individual C. elegans over times of ∼1 hour after removal from food, using two custom imaging set-ups that allow us to track animals on large ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…A non-zero drift magnitude k ψrms = 0 indicates that in addition to purely random (diffusive) changes in orientation, there is an underlying bias (i.e. directional persistence) in the worms' turning over 100 s windows, consistent with previous studies in larger arenas [23].…”
Section: Diffusive Turning With Driftsupporting
confidence: 86%
“…A non-zero drift magnitude k ψrms = 0 indicates that in addition to purely random (diffusive) changes in orientation, there is an underlying bias (i.e. directional persistence) in the worms' turning over 100 s windows, consistent with previous studies in larger arenas [23].…”
Section: Diffusive Turning With Driftsupporting
confidence: 86%
“…A non-zero drift magnitude k crms = 0 indicates that in addition to purely random (diffusive) changes in orientation, there is an underlying bias (i.e. directional persistence) in the worms' turning over 100 s windows, consistent with previous studies in larger arenas [23].…”
Section: Diffusive Turning With Driftsupporting
confidence: 86%
“…The worm's behavioural repertoire [16,17] is commonly characterized in terms of forward motion occasionally interrupted by brief reversals [18][19][20], during which the undulatory body wave that drives its movement [21] switches direction. In addition, worms reorient with a combination of gradual curves in the trajectory (weathervaning) [22,23] and sharp changes in body orientation (omega-turns [19] and delta-turns [24]). These elementary behaviours are combined in exploring an environment [22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Under poor environmental conditions in which C. elegans is far from food resources, it crawled around the field to search for food resources. A previous study quantitatively characterized this behavior and reported that a locomotory behavior under these conditions has a long-range directionality and cannot be explained by a simple random isotropic model of locomotion [ 19 ]. Wild-type animals moved in an apparently unbiased manner when placed on a plate without any chemicals or food (Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, to quantitatively measure the extent to which animals made directional tracks, we performed the analysis based on fractal analysis as described previously [ 19 ]. Briefly, the trajectory of each animal was divided into segments with length of size δ (mm), and the sum of linear distances of adjacent dividing points was computed as L δ (mm).…”
Section: Resultsmentioning
confidence: 99%